Some observations on swarming in nature and colony foundation under laboratory conditions in Odontotermes assmuthi (Holmgren) at Dera Dun (Isoptera: Termitidae). - Sen-Sarma, Parimal Kumar (Contributions to Entomology = Beiträge zur Entomologie, 1962)
In this paper the process of swarming in nature and colony foundation under laboratory conditions in Odontotermes assmuthi (Holmg.) has been described. - 1. Swarming behaviour is described in detail on the basis of field observations. Flight of alates occurs in the fourth week of June and always at about 4.30 p.m. Swarming follows immediately after a heavy shower. - 2. The process of wing shedding is described. - 3. The calling attitude to attract males is taken up by females only after wing shedding. Female abdomen is raised up and moved violently until contact with a male takes place. Attraction of males towards the female in calling attitude appears to be visual and not a result of scent signals. - 4. Observations on tandem behaviour have been recorded. - 5. In colony foundation, nesting site is selected by females. Eggs are laid after some 6-9 days of swarming. Number of first batch of eggs varies from 100-130. Temporary cessation of egg laying takes place after the laying of first batch of eggs. The second batch of eggs are laid 3 days after the hatching of first batch of eggs, and egg laying thereafter becomes a continuous non-stop process. Incubation period is 40-42 days. In hatching parental care of eggs appears essential. Both sexes take care of the eggs and young. Parthenogenesis has not been observed.